(3JNejS HGfJ SYGO dcYH Hf RgjQs - (3eLghds; (3cYH Hf RgjQ , CHh GdeZQH,J (B26 (3g` s
(3ChdgG (B:s
(3aEfi deG hbaJ Ydi GdbUjOI GdeTghQI HHGfJ SYGO dcYH Hf RgjQ Hf CHj Sdei Oei HSjja Gdghi hGdgLQ eWdhd hYbO UHQi Yf GdCMHGH eMdhd hOeY Yjfi Yf GdEQLGa ehUhd HGfJ SYGO abdHi Gdjhe eJHhd s
(3BNQgG (B:s
(3GdUdGI Ydi GdeNJGQ SjOfG NjQfG OjfG heQTOfG hNjQ OGY dehdGfG hefLOfG hBdg GdeUWajf GdZQ JYbOfG eGMQcJ ahb CTLGQ YKGcjd s
(3Vef eLehY , JQJjHgG (B: (3ef U (B275(3H (B- (3U(B279(3Hs
(3GfXQg eY HZjI GdBed ai JQJjH GdcGeds
(3ddeHQOs
(3fSNI KGfjIs
(3JHUQI GdYfhGf (B:s
(3JNejS TYQis
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdCOHs